POTENCIAL ANTI-INFLAMATÓRIO, ANTIMICROBIANO E ANTIBIOFILME DAS FOLHAS DE MICONIA ALBICANS (MELASTOMATACEAE) - Djaceli Sampaio de Oliveira (2023)
The Miconia albicans (Melastomataceae) is popularly known as canela-de-velho, and its leaves are used as tea to treat inflammation and joint pain. However, few scientific evidence evaluates the in vivo anti-inflammatory potential correlated to the chemical profile and seasonal interference of the compounds. In this sense, was developed a M. albicans aqueous extract (MAAE), similar to use by the population, and used to inflammation, analgesia, and toxicity assays. It revealed that the MAAE at a dose of 256 mg/kg, inhibits the edematogenic effect in treated animals, as well as reduces the level of leukocyte migration, against the acute inflammatory response. The acetic acid-induced abdominal writhings were decreased with MAAE treatment, as well as the paw licking time response was reduced, showing nociceptive potential. MAAE showed no toxicological effects, as evaluated in acute and repeated-dose toxicities. The animals showed no alterations when the biochemical, histological and hematological parameters were analyzed. The antimicrobial and antibiofilm activities of MAAE and 4 fractions were evaluated against Staphylococcus aureus and Pseudomonas aeruginosa bacteria, all samples submitted did not show effective activity against the pathogenic strains. The phytochemical analysis by the CLAE-DAD- EM technique, made it possible to identify 24 compounds from the MAAE, such as megastigmanes, flavonoids, ellagitannins and triterpenes, highlighted that these classes of metabolites are recognized for their anti-inflammatory potential. In the seasonal investigation, 4 individuals of the same species were monitored for 10 months, this way, it was observed, that the dry and rainy seasons interfere in the production of secondary metabolites of the plant. Was observed the classes of flavonoids and megastigmanes occur with greater intensity in the dry season, while tannins occur more intensely during the rainy season. In this work, the class of megastigmanes was identified for the first time in the genus Miconia, and there was not information about the season variation related to these compounds.